Empowered by Enterprise: Evaluating Livelihood Status Improvement through Attracting and Retaining Youth in Agriculture (ARYA) - Mohanty, Priya Ranjan; Sahoo, Madhusmita; Ghosh, Souvik (Indian Journal of Extension Education, 2025)
The ARYA initiative by ICAR has effectively engaged rural youth in agriculture, promoting financial gain and interest in agripreneurship. ARYA project has transformed the agricultural landscape by retaining rural youth in the sector and empowering them with essential skills and opportunities. This study was conducted in Puri district of Odisha during 2024,aiming to assess farmers’ livelihood status of ARYA entrepreneurs. A total 120 respondents were surveyed using structured interviews and secondary data sources. The results revealed that the overall mean score of livelihood status increased by 21%, demonstrating the programme’s success in ensuring sustainable livelihoods and income with minimal investments. Participants have shown significant improvements in their livelihood index, social participation, and information seeking behavior. This initiative has significantly contributed to the socio-economic development of rural areas, highlighting its role in driving sustainable change and fostering a resilient agricultural community. The positive outcomes of the ARYA initiative underscore its importance in promoting sustainable agricultural practices and enhancing the overall livelihood status of the rural youth.